Institutional deployment of spatial computing for intraoperative visualization in surgery and procedural medicine - Nikita S. Thareja; Emily Mitchell; Sonia Sekhon; Ana Garcia Cabrera; J. Jeffery Reeves; Hannah Hollandsworth; Bryan Sandler; Garth Jacobsen; Bobby Korn; George Cheng; Ryan C. Broderick (npj Digital Surgery, 2026)
Abstract Augmented reality (AR) head-mounted displays enable customizable intraoperative visualization of surgical video and ancillary data. However, real-world experience with implementation in surgical environments remains limited. We describe the first institutional deployment of the Apple Vision Pro (AVP; Apple Inc., Cupertino, CA, USA) across multiple surgical and procedural services within a single academic medical center. We conducted a prospective observational cohort study from August 2024 to January 2026. AVP was deployed as the primary visualization platform across operating rooms, an ambulatory surgery center, and procedural suites for minimally invasive surgery (MIS), interventional pulmonology (IP), and oculoplastic surgery (OP). Conventional monitors were maintained as backup. Primary outcomes included intraoperative safety events, workflow interruptions, and headset utilization. Exploratory outcomes included user feedback and NASA Task Load Index (NASA-TLX) scores. Thirty-five users employed AVP during 174 procedures (136 MIS, 30 IP, and 8 OP), representing 227 headset uses. No AVP-attributable intraoperative complications, conversions, or adverse events occurred; headsets required removal in 6 cases (2.6%). NASA-TLX scores decreased with exposure, suggesting a learning curve that varied by training level. AR spatial computing was safely integrated for surgical visualization across diverse workflows, providing a framework for institutional adoption of AR technologies in the digital operating room.